Small intestinal mucosal abnormalities in relatives of patients with dermatitis herpetiformis. Issue 6 (June 1970) - Marks, Janet; Birkett, David; Shuster, Sam; Roberts, D. F.
Abstract : Jejunal biopsy has been carried out in 19 relatives of patients with dermatitis herpetiformis and stereomicroscopic abnormalities have been found in seven. The majority of the relatives in whom these abnormalities were found had no bowel symptoms: one had the rash of dermatitis herpetiformis. All but one of the propositi of the relatives in whom were found small intestinal mucosal abnormalities themselves had the coeliac syndrome. It is concluded that a genetic factor is involved in the production of the enteropathy of dermatitis herpetiformis as in other forms of the coeliac syndrome.